Production and characterization of chitooligosaccharides by the fungal chitinase Chit42 immobilized on magnetic nanoparticles and chitosan beads: selectivity, specificity and improved operational utility. Issue 10 (29th January 2021) - Kidibule, Peter E.; Costa, Jessica; Atrei, Andrea; Plou, Francisco J.; Fernandez-Lobato, Maria; Pogni, Rebecca
Abstract : Chitin-active enzymes are of great biotechnological interest due to the wide industrial application of chitinolytic materials. Abstract : Chitin-active enzymes are of great biotechnological interest due to the wide industrial application of chitinolytic materials. Non-stability and high cost are among limitations that hinder industrial application of soluble enzymes. Here we report the production and characterization of chitooligosaccharides (COS) using the fungal exo -chitinase Chit42 immobilized on magnetic nanoparticles and food-grade chitosan beads with an immobilization yield of about 60% using glutaraldehyde and genipin linkers. The immobilized enzyme gained operational stability with increasing temperature and acidic pH values, especially when using chitosan beads-genipin that retained more than 80% activity at pH 3. Biocatalysts generated COS from colloidal chitin and different chitosan types. The immobilized enzyme showed higher hydrolytic activity than free enzyme on chitosan, and produced COS mixtures with higher variability of size and acetylation degree. In addition, biocatalysts were reusable, easy to handle and to separate from the reaction mixture.